ANALYSIS OF TRADITIONAL SPORTS GAMES IN DEVELOPING COOPERATIVE CHARACTERS IN EARLY CHILDREN - Raguan, Siti; Rahmadi, Rahmadi; Rakhman, Arie (Riyadhoh : Jurnal Pendidikan Olahraga, 2024)
The research aims to identify a number of data related to the process of developing symbols and the cultural values created. Traditional sports games in the current era are increasingly being replaced by digital games. The type of research used is descriptive research. Researchers conducted open interviews which initially carried out in-depth observations in order to see the problem. It can be seen that the problem is that many students at SDN Tanipah school are influenced by gadgets and often play gadgets, namely games in them, so that it is influenced in the formation of the students' character in controlling themselves to communicate, work together and be responsible in it. The research results obtained in the acceptance of traditional sports games in schools are because in modern developments these games are able to become an alternative to digital games which influence the character of students. These traditional sports games are able to become a forum for character building for students at an early age today.